Field emission characteristics of a nanotube-fullerene composite: a theoretical study. (28th April 2021) - Xu, Shunfu; Feng, Huaiwei; Zhang, Yuming; Liu, Weihui; Li, Chun; Yuan, Guang
Abstract: First-principles calculations are used to investigate electronic and field emission characteristics of a nanotube-fullerene composite (a single-walled carbon nanotube (CNT) with a C20 molecule), which indicate that emission currents of the CNT-fullerene composite under external electric fields are roughly four times higher than those of original carbon nanotubes, and its pentagon on the apex is the highest probable positions for electron emission. Moreover, work functions of the CNT-fullerene composite decrease linearly with applied electric fields. The remarkable influence of lithium adsorption on electronic and field emission characteristics of the CNT-fullerene composite is also investigated. After lithium adsorption, the work functions of the CNT-fullerene composite decline evidently, while the emission currents increase polynomially. The emission currents of the adsorption system have been improved by two orders of magnitude (with an order of 10 −4 A), and the lithium adatom above on the apex is the most probable position for emission.